2020
DOI: 10.1038/s41591-019-0695-9
|View full text |Cite|
|
Sign up to set email alerts
|

Human and mouse single-nucleus transcriptomics reveal TREM2-dependent and TREM2-independent cellular responses in Alzheimer’s disease

Abstract: Glia have been implicated in Alzheimer’s disease (AD) pathogenesis. Variants of the microglia receptor TREM2 increase AD risk and activation of “disease-associated microglia” (DAM) is dependent on TREM2 in mouse models of AD. We surveyed gene expression changes associated with AD pathology and TREM2 in 5XFAD mice and human AD by snRNA-seq. We confirmed the presence of Trem2 -dependent DAM and identified a novel Serpina3n + C4b + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

74
884
10
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 801 publications
(1,041 citation statements)
references
References 62 publications
74
884
10
3
Order By: Relevance
“…From the perspective of actual drug repurposing only the later compounds are useful. In other studies, gene expression changes have demonstrated increased interferon signaling in AD 65 and in ALS 66 brains. Recently, we have found that cytoplasmic dsRNA, a known activator of Type I interferon, is present in ALS brains with TDP-43 pathology.…”
Section: Discussionmentioning
confidence: 84%
“…From the perspective of actual drug repurposing only the later compounds are useful. In other studies, gene expression changes have demonstrated increased interferon signaling in AD 65 and in ALS 66 brains. Recently, we have found that cytoplasmic dsRNA, a known activator of Type I interferon, is present in ALS brains with TDP-43 pathology.…”
Section: Discussionmentioning
confidence: 84%
“…41 Colonna's laboratory is also using scRNA-seq and single nucleus RNA sequencing (snRNA-seq) to understand the transcription patterns of other types of cells in the brain and how the TREM2 variants observed in patients with Alzheimer's disease affect microglial gene expression in humans. 42 He suggested that pharmacological activation of microglial receptors may be a therapeutic strategy for Alzheimer's disease.…”
Section: Targeting Microglial Activity Via Trem2mentioning
confidence: 99%
“…The increased expression is strongly associated with an increase in reactive A1 astrocytes in the EU LA. Reactive A1 astrocytes have been shown to cause neuronal stress and eventual cell death, and have been reported in patients with several neurodegenerative diseases including AD [25][26][27] . Future studies are needed to identify the mechanism producing this expression difference.…”
Section: Mainmentioning
confidence: 99%